2018
DOI: 10.5897/ajar2018.13316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of important morphological traits in Mozambican sorghum [Sorghum bicolor (L.) Moench] germplasm using multivariate analysis

Abstract: Classification of sorghum [Sorghum bicolor (L) Moench] breeding material based on multiple crucial characters is important towards the possible formation of homogeneous groups of genotypes and groups that can be exploited in the identification of parents for use in a breeding program. The objective was to determine the morphological characters that distinguish desirable breeding material and group the genotypes of sorghum according to similarity. Principal component analysis (PCA) and cluster analysis were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Results in Table3revealed that genotypes; Willy, William, and Atlas out yielded high values of juice extraction % (34.28, 39.82, and 4.69 %) and juice yield (4.87, 5.24 and 4.69 ton/fed), respectively indicating their magnitude as promising genotypes that may be used in breeding programs of sweet sorghum. The current results are harmonized with many previous investigations reported byAbd El-Raheem et al (2010),Rao et al (2013),Erdurmus et al (2018),Mulima et al (2018),Khidr et al (2021) andYücel et al (2022) who confirmed that the considerable variability among the assessed sweet sorghum genotypes considering the juice quality readings provides a real chance to improve the juice productivity of sweet sorghum crop and its extracts and other products.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Results in Table3revealed that genotypes; Willy, William, and Atlas out yielded high values of juice extraction % (34.28, 39.82, and 4.69 %) and juice yield (4.87, 5.24 and 4.69 ton/fed), respectively indicating their magnitude as promising genotypes that may be used in breeding programs of sweet sorghum. The current results are harmonized with many previous investigations reported byAbd El-Raheem et al (2010),Rao et al (2013),Erdurmus et al (2018),Mulima et al (2018),Khidr et al (2021) andYücel et al (2022) who confirmed that the considerable variability among the assessed sweet sorghum genotypes considering the juice quality readings provides a real chance to improve the juice productivity of sweet sorghum crop and its extracts and other products.…”
supporting
confidence: 91%
“…Genotypes that evolved in the same area were grouped into different clusters. Genetic divergence among sweet sorghum genotypes using cluster analysis was reported by (Zhan et al, 2012;Jain and Patel, 2016and Mulima et al, 2018and Naoura et al, 2020.…”
Section: Ejpbmentioning
confidence: 91%
See 2 more Smart Citations
“…The eigenvalues indicated the variance accounted for by the corresponding principal components or eigenvectors. Principal component analysis has been known as complementary to cluster analysis (Mulima et al 2018). Therefore, combination of these two methods was commonly applied in plant systematics studies in various plant taxa at any taxonomic level, from species (Fitriana and Susandarini 2019;Singh et al 2020), genus (Alzahrani et al 2021), to family (Arogundade and Adedeji 2019).…”
Section: Phenetic Relationships Of Species and Varieties Of Dicranopteris And Sticherusmentioning
confidence: 99%